Kritik als Ideologie: Selbstreflexion und Herrschaftsanteile der akademischen Linken - Reitz, Tilman (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
This contribution discusses recent debates on the adequate form of ‘critique’ with a meta-critical intention. Since the partisans of academic critique typically fail to account for the effects of their own institutional embeddedness, their methodological reflections neutralize oppositional demands and turn political struggle into a scholastic exercise. In an extension of this analysis, the article aims to show how the academic class over-estimates its potential for bringing about liberating political change, how it falsely generalizes its own conditions of existence, and how it really contributes to the justification of capitalist power structures. The suspicion that recent populist attacks on the ‘elite’ have a fundament in progressive-liberal coalitions thus finds support in the practice of progressive discourse.